Rancang Bangun Cloud Storage untuk Coworking Space Berbasis Raspberry Pi - Harnan Malik Abdullah; Hendi Nugroho (Program Pendidikan Vokasi Universitas Brawijaya, 2018)
Coworking space is a place used as a work environment shared by communities or people who share the same vision. For collaboration activities, data files are often exchanged among the people involved. The use of portable storage media for file exchange becomes less effective for collaborative work. This study aims to implement cloud storage technology to see the performance that is used as a medium for data storage that can be accessed on the local network. The cloud storage is implemented using Raspberry Pi 3 hardware and an external hard drive. The software uses the Raspbian Pixel operating system with Nimbus applications to run cloud storage functions. The test results show that the system runs well in functionality. System performance is studied based on CPU usage indicating that maximum 5 users can perform concurrent data file upload activity for file size less than 100MB. Whereas if the file size is more than 1GB, only 3 clients can be served simultaneously.